Waldenström's macroglobulinaemia in a bird breeder: a case history with pulmonary involvement and antibody activity of the monoclonal IgM to canary's droppings. - James, J M (1987)
A canary breeder with Waldenström's macroglobulinemia developed a pulmonary disease related to an interstitial infiltration by malignant B cells secreting a monoclonal IgM K. The serum monoclonal IgM was shown to possess an antibody activity to some canary's droppings antigen. This finding may help elucidate the natural course of lymphoid malignancies and the pathogenesis of rare visceral localizations.